ANALISIS YURIDIS PELANGGARAN PASAL 40 AYAT 2 HURUF (E) UNDANG - UNDANG NOMOR 2 TAHUN 2014 TENTANG SAKSI DALAM AKTA OTENTIK - FATIA ZAHRA (PREMISE LAW JURNAL, 2017)
A witness, in general, is someone who provides an oral or written testimony describing what he himself sees (waarnemen) someone’s action or deed or a situation or an event. In every legal event, including the making of a certificate by a notary, the witnesses must be presented. They are themselves the ones who witness and see the legal event. Two kinds of witness are recognized in the notary, instrumental witness and known witness. An instrumental witness is an absolute witness obliged to be present at the making of a certificate by a notary and a known witness is a witness introduced to the notary by the person appearing. Article 40 of Law No.2/2014 on position of notary regulates about this witness where terms of a witness are stipulated. One of the terms is that a witness in not allowed to have a marital relationship or blood relationship in a straight line above or below without degree limitation and side line to the third degree to the notary or the parties. Keywords: Keywords: Juridical Normative, Witness, Authentic CertificateA witness, in general, is someone who provides an oral or written testimony describing what he himself sees (waarnemen) someone’s action or deed or a situation or an event. In every legal event, including the making of a certificate by a notary, the witnesses must be presented. They are themselves the ones who witness and see the legal event. Two kinds of witness are recognized in the notary, instrumental witness and known witness. An instrumental witness is an absolute witness obliged to be present at the making of a certificate by a notary and a known witness is a witness introduced to the notary by the person appearing. Article 40 of Law No.2/2014 on position of notary regulates about this witness where terms of a witness are stipulated. One of the terms is that a witness in not allowed to have a marital relationship or blood relationship in a straight line above or below without degree limitation and side line to the third degree to the notary or the parties.